Kostel, prazgodovinska naselbina - Velušček, Anton; Dirjec, Janez (Arheološki vestnik, 1996)
Results are presented from test excavations at the elevated settlement of Kostel in 1982 and 1983. The excavations were directed by M. Hirschback-Merhar. The authors date the prehistoric elevated settlement to the early and middle Eneolithic, and to the end of the middle Bronze Age and the beginning of the late Bronze Age, as well as to the late Bronze Age.